Demographic Features and Etiology of Congenital Hypothyroidism at the National Diabetes and Endocrine Center in Oman from 2004 to 2016 - Mohammed Al Jafari; Sachin Jose; Aisha Al Senani (Oman Medical Journal, 2020)
Objectives: Congenital hypothyroidism (CH) is the most common endocrine disorder in neonates as well as one of the few preventable causes of severe learning difficulties. Early screening, diagnosis, and treatment are mandatory to prevent later sequelae. We sought to determine the demographic and the clinical features of CH in Oman. Methods: We conducted a retrospective cross-sectional study, including all Omani children newly diagnosed with CH from January 2004 to December 2016 followed at the National Diabetes and Endocrine Center at the Royal Hospital. Those with transient hypothyroidism were excluded from the study. Data collection involved demographic data, clinical manifestations, lab investigations, thyroid scan results, and initiation date of the thyroxine (T4). Results: A total of 96 patients were newly diagnosed with CH during the study period. Out of the 96 patients, 43 were males (44.8%), and 53 were females (55.2%), and majority were asymptotic (n = 84; 87.5%). Only 78 patients had a thyroid scan. Among those who did the scan, thyroid dysgenesis was the most common (n = 40, 51.3%), followed by dyshormonogenesis (n = 35; 44.9%) and the least was central hypothyroidism (n = 3; 3.8%). The majority of patients (n = 72; 86.7%) were started on T4 therapy within 30 days of life. The remaining (n = 11; 13.3%) had a delay in starting the treatment due to compliance issues, which led to a developmental delay (p < 0.001). Conclusions: This is the first epidemiological study conducted in Oman that highlights the unique demographic and etiology features of CH. Dyshormonogenesis has a high prevalence in the Omani population compared to other nations. The neurological sequelae in our patients were higher in compression to worldwide prevalence, which was mainly due to delay in starting T4 therapy.